Understanding the Principles of Islamic Banking and the Development of Islamic Banking - Icha Afrillia Hidayat; Febyviani Dwimutian Anggraini; Muhammad Ryas Fatiha Kesuma; Heni Noviarita (Al-Fadilah: Islamic Economics Journal, 2025)
Understanding the basic principles of Islamic banking and the dynamics of its development is crucial, both from a theoretical and practical perspective. These principles, which include the prohibition of riba (usury), gharar (gharar), and maysir (gambling), as well as the application of the principle of profit and loss, play a crucial role in establishing a fair and transparent banking system. Furthermore, Islamic banking in Indonesia has experienced significant growth over the past few decades, despite challenges related to public education, regulation, and public acceptance. This study uses a qualitative approach with descriptive-analytical methods to delve deeper into the core principles of Islamic banking and analyze the sector's development in the Indonesian context. The findings reveal that despite the rapid growth of Islamic banking, challenges remain to be addressed to enhance Islamic financial inclusion, including product issuance, regulatory frameworks, and public awareness. This study contributes to a deeper understanding of Islamic banking principles and provides insights into the future direction of the Islamic banking sector.